Stereotip Antara Penduduk Asli dan Pendatang di Kota Sorong – Papua Barat Daya - Abduh, Ichsan Muhammad; Hasrullah , Hasrullah; Cangara, Hafied; Pulubuhu, Dwia Aries Tina (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to describe the perspectives/stereotypes towards each other between the indigenous and immigrant populations in the Sorong City area. The indigenous Papuan population is defined as the population that falls into 3 criteria, namely those whose father/mother is of indigenous Papuan descent, or one of whose parents is of Papuan descent, and people who have been traditionally adopted as indigenous Papuans, while the immigrant population group is a non-Papuan population that comes from all over the Indonesian archipelago. The research used a qualitative method by interviewing 5 informants from each group. The results showed that both groups collectively claimed themselves to be part of the Papuan community. The indigenous people view the newcomers based on two criteria: ethnic status and their role in contributing to the Papuan community in Sorong City. Ethnically, newcomers are those who do not have Papuan bloodlines from either or both parents, resulting in the label of